Additive manufacturing in the construction industry : the comparative competitiveness of 3D concrete printing - Khajavi, Siavash H. (2021)
The construction industry is facing increasing pressure to improve productivity and decrease its environmental impact. Additive manufacturing (AM) technologies, especially three-dimensional concrete printing (3DCP) technology, have provided many benefits for construction. However, holistic comparative studies of the competitiveness of 3DCP and conventional methods, from cost and time perspectives, are lacking. Choosing between the methods is difficult for practitioners. In this study, we investigated the current state of 3DCP in the construction industry using seven distinct scenarios. Our analysis was performed to illustrate the impact of design and supply chain configurations on performance. The results prove the notable competitiveness of 3DCP. In contrast to the conventional construction method, the more complex round design had a positive impact on the cost and process time in 3DCP scenarios. Additionally, we show that on-site 3DCP using a robotic arm was more cost-effective than off-site 3DCP.